ha13_176a_FineScaleTagData - Miller, P. J. O.; Kvadsheim, P. H.; Lam, F. P. A.; Tyack, P. L.; Curé, C.; DeRuiter, S. L.; Kleivane, L.; Sivle, L. D.; Van IJsselmuide, S. P.; Visser, F.; Wensveen, P. J.; Von Benda-Beckmann, A. M.; et al. (Dryad Digital Repository, 2015)
Time-series data of northern bottlenose whale subject in the study.